Pembagian Warisan Menurut Hukum Islam - Sarjiyati Sarjiyati (JURNAL DAYA-MAS, 2019)
Indonesia is known as a predominantly Muslim country. The law of inheritance of Islam occupies a very important place in Islamic Law. The verses of the Qur'an govern the law of inheritance clearly and in detail. This is understandable because the inheritance problem must be experienced by everyone and it is easy to cause disputes between heirs. The method used in this activity is the counseling to the community and discussion. The result of the discussion can be concluded that: Group of heirs by sex there are 25 people consisting of 15 men and 10 women. Sections of the heirs according to Islamic Law, that is, one gets 1/2 of the inheritance, 2/3 of the estate, 1/3 of the estate, 1/4 of the estate, 1/6 of the estate, 1 / 8 of the estate, Acquires all inheritance, inheritance is equally divided, obtaining the remainder, depending on the position of the heirs.